Sistem Penetasan Artemia dan Pemberian Pakan Burayak Ikan Guppy Otomatis Berbasis Mikrokontroler - Hendi Suhendi; Ogi Rahmansyah (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
Guppy fish (Poecilia reticulata) cultivation requires special attention, especially in terms of feeding the fry, which must be done regularly and consistently. One of the best feeds for fry is Artemia, but the process of hatching and feeding manually often makes it difficult for farmers. This study aims to design and implement an automated system that is able to hatch Artemia and provide food to guppy fry on a schedule using an Arduino Mega 2560 microcontroller and NodeMCU ESP8266. The system is equipped with various sensors such as DS18B20, DHT11, and ultrasonic, as well as actuators such as servo motors, DC motors, and DC water pumps. Feed scheduling is managed using an RTC module and can be monitored through the Telegram interface in real-time. Test results show that the system can hatch Artemia semi-automatically within 24 hours, where the operator still presses a button or starts each cycle, but the movement, position and speed are automatically controlled by the servo and controller, thus providing feed automatically and on time three times a day, and sending status notifications via Telegram with a fast response. This system has been proven to increase efficiency and accuracy in the guppy fish cultivation process and provides a practical automation solution for farmers. This study uses the Research and Development (R&D) method with a systems engineering approach. This method was chosen because it is suitable for designing and developing an Artemia hatching system and automatic feeding. This study designed and implemented a semi-automatic Artemia hatching system that can hatch Artemia eggs and distribute them as food for guppy fry on a scheduled and automatic basis. The system is also equipped with remote monitoring and control features via a Telegram Bot based on the ESP8266 microcontroller and Arduino Mega.